PHYSIOLOGY TEACHING IN THE PBL (PROBLEM-BASED LEARNING) CONTEXT: REPORT OF WORKSHOPS DEVELOPED IN BRAZIL - Dal Bosco, Lidiane (2021)
The workshop entitled “Physiology teaching in the Problem-based learning (PBL) context” was developed in two different times and contexts, in Brazil during 2017 and 2018. The main goal was to show how PBL works and discuss different possibilities and strategies to include physiology education in this different context of non-traditional teaching, where the role of professor changes. The workshop was highly valuable, gave an initial basis on PBL to the participants and stimulates them to think about the possibilities of PBL use and the potentials of this method, in both contexts of application.